Perancangan Interior Fasilitas E-Sports Arena - Julius, Erwin; Honggowidjaja, Stephanus P; tedjokoesomo, purnama esa dora (Intra, 2016)
T This Design’s background are the problems of the growth of gaming industries in Indonesia and have been made official by the government that gamers can be national athlete through many steps but they still don’t have the place with facilities and appreciation, so this E-Sports facility maximize their potential and change the way people think about the game that gamin isn’t just for fun but gaming can be a profession. The implementation of futuristic design will be the furniture and interior elements to create the impression of a futuristic design.